Womanism or Humanism: The Exploration of Pamela Smith’s Translation for Ogun Qmode (2024)
Language choice in translation may be informed by many factors. Some scholars have alluded this to translator’s educational background, faithfulness to source text, their personality in the area of religious preference, condition of service and so on. The examination of the impact of gender or the sex of the translator on the language choice in the translation has not been as prominent. This paper explores the translation of Pamela Smith with the view to determining whether her gender influences her choice of words and style within the theoretical framework of natural equivalence. It was found that the language choice of the translator was full of compassion, romanticism and dynamism, which are a blend of womanism and humanism.